Cervical Adenocarcinoma in Situ in the United States: Results from Population-based Laboratory Surveillance, 2008–2014. (4th October 2017) - Cleveland, Angela Ahlquist; Johnson, Michelle L; Gargano, Julia W; Park, Ina U; Griffin, Marie R; Niccolai, Linda M; Schafer, Sean; Bennett, Nancy M; Markowitz, Lauri E; Unger, Elizabeth R
Abstract: Background: Cervical cancer screening methods are more effective for detection of squamous cell carcinoma precursor lesions (cervical intraepithelial neoplasia; CIN2 and 3) than for less-common adenocarcinoma precursors (adenocarcinoma in situ; AIS). Primary prevention through human papillomavirus (HPV) vaccination is expected to impact both CIN and AIS, although less data exist about the HPV types associated with AIS. We analyzed HPV types detected in AIS and CIN identified through population-based surveillance. Methods: The Centers for Disease Control and Prevention and partners conduct surveillance for CIN2, CIN3, and AIS (CIN2+) among women aged ≥18 years in five locations in the United States. Specimen blocks for women aged 18–39 are sent to CDC for HPV typing using L1 consensus PCR. We analyzed cases with AIS only, AIS with CIN2 or 3 (AIS+CIN), and CIN3 only, the highest grade squamous cell precursor. We used chi-square tests to compare HPV types by histology. Types evaluated were HPV16 and 18 (high-risk (HR) types targeted by all HPV vaccines), 5 additional HR types targeted by the 9-valent vaccine (31/33/45/52/58; "additional 9vHPV"), and 7 other HR non-vaccine types (35/39/51/56/59/66/68). Results: Between 2008 and 2014, 18, 394 women were diagnosed with CIN2+. Of those, 517 (2.8%) had AIS (283 AIS only, 234 AIS+CIN) and 5, 766 (31%) had CIN3 only. Median ages at diagnosis for AIS, AIS+CIN, and CIN3 were 37, 32, and 31 years, respectively. HPV typing results were available for 89 AIS, 99 AIS+CIN, and 2, 923 CIN3 cases; HPV was detected in nearly all specimens (99% AIS, 100% AIS+CIN, 98% CIN3), and 21% of positive specimens had >1 HPV type identified. HPV16 (AIS: 51%, AIS+CIN: 64%, CIN3: 59%; p ≤ 0.001) and HPV18 (AIS: 39%, AIS+CIN: 31%, CIN3: 5%; P ≤ 0.001) were most common. Additional 9vHPV types (AIS: 3%, AIS+CIN: 12%, CIN3: 26%; P ≤ 0.001), and HR non-vaccine types (AIS: 6%, AIS+CIN2+: 2%, CIN3+: 9%; P ≤ 0.001) were detected less frequently. Conclusion: HPV types differed by histology, with AIS having a greater proportion of HPV 18 and a lower proportion of additional 9vHPV and HR non-vaccine types. This report on the largest sample of genotyped AIS cases to date provides data for vaccine impact monitoring, and suggests a high opportunity for vaccine prevention of AIS. Disclosures: M. R. Griffin, MedImmune: Grant Investigator, Grant recipient